How do novel and conventional agri-food wastes, co-products and by-products improve soil functions and soil quality?. (15th July 2020) - Gebremikael, M.T.; Ranasinghe, A.; Hosseini, P.S.; Laboan, B.; Sonneveld, E.; Pipan, M.; Oni, F.E.; Montemurro, F.; Höfte, M.; Sleutel, S.; De Neve, S.
Highlights: Low value agri-food wastes, co-products and by-products (AFWCBs) improve soil quality. Insect frass residues suppress plant disease, increase microbial activities and immobilize N. Digestates, duckweed and rice bran compost release N immediately after application. AFWCBs play roles in closing the nitrogen and carbon cycle. Abstract: Agriculture is estimated to generate about 700 million tons of waste annually in the EU. Novel valorization technologies are developing continuously to recover and recycle valuable compounds and nutrients from waste materials. To close the nutrient loop, low-value agri-food wastes, co-products and by-products (AFWCBs) produced during the valorization process, need to be returned to the soil. However, knowledge on their reaction in soils that is needed to allow efficient and environmentally sound recycling is largely lacking. To this end, we set up a series of laboratory incubation experiments using 10 AFWCBs including insect frass residues made from three different feedstocks, anaerobic digestates from two feedstocks, potato-pulp, rice bran compost, duckweed and two reference crop residues (wheat straw and sugar beet) and measured net N release, C mineralization, dehydrogenase activity (DHA), microbial biomass C (MBC) and community structure. The suppressing potential of frasses and digestates against Rhizoctonia solani was determined using bean. The digestates released the highest net mineral N (50–70%) followed by rice bran compost (55%) and duckweed (30%), while frass made from general food waste and potato-pulp immobilized N like the reference straw for 91 days after incubation. All AFWCBs except digestates significantly increased MBC compared to the control while frasses, potato-pulp and duckweed increased DHA. Frasses and digestates significantly suppressed the development of Rhizoctonia solani in bean plants. AFWCBs from emerging valorizing technologies have the potential to improve microbial activities, C sequestration and may play a significant role in closing the nutrient loop.